Psychosocial Determinants of Health Behaviour Change in an E-Counseling Intervention for Hypertension. (20th December 2011) - Durrani, Samir; Irvine, Jane; Nolan, Robert P.
Abstract : We evaluated the influence of psychological stress and depression on motivation to adhere to recommended guidelines for exercise and diet. This study was conducted within a larger e-counseling trial. Subjects diagnosed with hypertension (n = 387, age = 44–74 years, 59% female) completed assessments at baseline and within 2 weeks after a 4-month intervention period. Outcomes included mean level of readiness to change diet and exercise and symptoms of depression and stress. Per protocol analysis defined e-counseling support as follows: ≥8 e-mails = therapeutic dose, 1–7 e-mails = subtherapeutic dose, and 0 e-mails = Controls. Baseline adjusted symptoms of depression and stress were inversely correlated with improvement in exercise (partial R = - . 14, P = . 01, and partial R = - . 17, P = . 01, resp.) but not diet or e-counseling. Subjects who received a therapeutic dose of e-counseling demonstrated greater readiness for diet adherence versus Controls (P = . 02 ). Similarly, subjects receiving a therapeutic level of e-counseling demonstrated significantly greater readiness for exercise adherence versus Controls (P = . 04 ). In sum, e-counseling is associated with improved motivation to adhere to exercise and diet among patients with hypertension, independent of symptoms of psychological stress and depression.